The relationship between cognitive change and physical health and behavioural outcomes in a Ugandan cohort of adults living with HIV – a longitudinal study. Issue 7 (3rd July 2019) - Spies, G.; Denckla, C. A.; Mall, S.; Levin, J.; Seedat, S.; Nakasujja, N.; Kinyanda, E.
ABSTRACT: We investigated changes in cognitive function and physical health and behavioural outcomes (HIV disease progression, health-seeking behaviour, adherence to HIV medications and risky sexual behaviour) at baseline and 12 months later among 1126 Ugandan adults living with HIV. Overall, cognitive function improved from baseline to follow-up, except for gait speed, which was slower at follow-up compared to baseline. There were improvements in physical health and behavioural outcomes by follow-up, with greater improvements among individuals on ART compared to those not on ART. Change in gait speed over time significantly predicted risky sexual behaviours at follow-up. This is the first study to investigate the longitudinal relationships between cognitive function and health outcomes among Ugandan adults living with HIV and provide insights into the possible links between cognitive function and negative clinical and behavioural health outcomes in people living with HIV.